2019
DOI: 10.1177/1076029619835053
|View full text |Cite
|
Sign up to set email alerts
|

Routine Coagulation Tests in Patients With Nonvalvular Atrial Fibrillation Under Dabigatran and Rivaroxaban Therapy: An Affordable and Reliable Strategy?

Abstract: Dabigatran and rivaroxaban, direct oral anticoagulants (DOACs), affect coagulation tests, and knowledge of their effects is important for therapeutic monitoring. Our aim was to examine the association between DOAC levels and routine coagulation tests in patients with nonvalvular atrial fibrillation. Samples from patients receiving dabigatran (150 mg) and patients receiving rivaroxaban (20 mg) were collected 2 hours after drug intake. Direct oral anticoagulant concentrations were determined using direct Hemoclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…In our study, a longer aPTT was significantly associated with reduced stroke severity and a smaller infarction volume in patients receiving dabigatran. aPTT has been experimentally reported to correlate with plasma dabigatran concentration in a curvilinear manner [19][20][21][22]. We speculate that a longer aPTT in patients on dabigatran may result in a smaller embolus size, enhanced embolus resolution, and reduced thrombus propagation, which may lead to decreased stroke severity [23,24].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In our study, a longer aPTT was significantly associated with reduced stroke severity and a smaller infarction volume in patients receiving dabigatran. aPTT has been experimentally reported to correlate with plasma dabigatran concentration in a curvilinear manner [19][20][21][22]. We speculate that a longer aPTT in patients on dabigatran may result in a smaller embolus size, enhanced embolus resolution, and reduced thrombus propagation, which may lead to decreased stroke severity [23,24].…”
Section: Discussionmentioning
confidence: 81%
“…Previous experimental studies have revealed a linear correlation between PT and plasma rivaroxaban concentration [12,17,21]. However, aPTT may not be suitable for the evaluation of rivaroxaban activity because of its unresponsiveness and poor sensitivity to this DOAC [27].…”
Section: Dabigatran Rivaroxaban B (95% Ci) P-value B (95% Ci) P-valuementioning
confidence: 99%
“…It would be interesting to have a reliable test to anticipate the therapeutic failure and then adapt a therapeutic strategy. In this regard a recent study suggests that the activity of anticoagulation measured by specific DOAC plasma levels on admission is associated with stroke severity (53), and some studies support the reliability of DOAC determination (54,55) especially in patients with acute ischemic stroke (56,57). However, the ideal test is not yet widely available, and more studies are needed to guide future treatment decisions (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen studies with a total of 1226 patients were included in the meta-analysis. Eight studies [22][23][24][25]38,47,56,57 that reported only the central tendency or dispersion, but not both, were excluded from the meta-analysis because the mean and standard deviation could not be estimated. Five studies 20,26,43,52,58 with significantly skewed estimated mean and standard deviation were excluded as this estimation method is not recommended.…”
Section: Meta-analysismentioning
confidence: 99%